Penerapan Bermain Mencocokkan Bentuk Geometri untuk Meningkatkan Kemampuan Mengenal Bentuk Geometri pada Anak Usia 4-5 Tahun di TK Islam Qalbin Salim - Rahayu, Asyla Dwi; Damayanti, Eka; Majid, Ahmad Farham; Bahar, Nurni Firdausi (Faculty of Tarbiyah and Teacher Training, 2025)
Improving the ability to recognize geometric shapes in children aged 4-5 years is very important, because this is the basis for children to understand the environment and basic mathematical concepts. This study aims to determine the increase in the ability to recognize geometric shapes after the application of the geometric shape matching play method in children aged 4-5 years. This community service research in the form of service learning was conducted at Qalbin Salim Islamic Kindergarten with the participation of 5 children. The instruments used were in the form of game tools in the form of matching geometric shapes to help the ability to recognize geometric shapes, observation sheets for children's achievement, and evaluation sheets for the implementation of the intervention. Data were analyzed using descriptive statistics to measure the increase in children's ability to recognize geometric shapes. The results of this community service research show that children are able to recognize and match geometric shapes with an 80% success rate in applying the method. The findings in this study imply that the geometric shape matching play method is effective in improving children's ability to recognize shapes, as well as providing a positive contribution to children's cognitive and fine motor development.